2021
DOI: 10.3390/w13162176
|View full text |Cite
|
Sign up to set email alerts
|

Numerical Analysis of Soil Water Dynamics during Spinach Cultivation in a Soil Column with an Artificial Capillary Barrier under Different Irrigation Managements

Abstract: Artificial capillary barriers (CBs) are used to improve root zone conditions as they can keep water and nutrients in the root zone by limiting downward percolation. Numerical analysis is one of the promising tools for evaluating CB systems’ performance during the cultivation of leafy vegetables. This study aims to investigate the effects of the CB system on soil water dynamics during spinach cultivation in a soil column under different irrigation scenarios using HYDRUS (2D/3D) by comparing uniform (UNI), line-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 32 publications
0
1
0
Order By: Relevance
“…Artificial capillary barriers are natural barriers to soil water movement under unsaturated conditions and, when properly designed and installed, can improve crop water use efficiency [9]. It has been demonstrated that mulching with various materials can decrease soil water evaporation, increase the amount of stored soil water that is available for plants, and reduce salt buildup in the soil [10].…”
Section: Introductionmentioning
confidence: 99%
“…Artificial capillary barriers are natural barriers to soil water movement under unsaturated conditions and, when properly designed and installed, can improve crop water use efficiency [9]. It has been demonstrated that mulching with various materials can decrease soil water evaporation, increase the amount of stored soil water that is available for plants, and reduce salt buildup in the soil [10].…”
Section: Introductionmentioning
confidence: 99%